Validity and Reliability of Cardiff Acne Disability Index in Turkish Acne Patients - (:unkn) unknown (DERI ZUHREVI HASTALIKLAR DERNEGI, 2010)
Background and Design: Acne is a common disease having profound affect on quality of life. Although various quality of life (QoL) scales have been developed, Cardiff Acne Disability Index (CADI) and Acne Quality of Life (AQOL) scale are most commonly used ones for research. The study aims to investigate the validity of CADI in Turkish acne patients. Material and Method: Sixty-eight consecutive acne patients were included for CADI validation. Test-retest procedure was performed with one week interval. Internal consistency and validity of the CADI was analyzed through Cronbach's alpha and Pearson's correlation analysis tests. Results: Cronbach's alpha value for the internal consistency of CADI was found to be 0.68, close to the satisfactory level, 0.7. Conclusion: CADI is an easy to use, time-sparing acne-specific QoL measure. However, since the validity is slightly below satisfactory level it should be used in combination with other measures to evaluate treatment outcome in clinical practice. (Turkderm 2010; 44: 25-7)
Keywords: Acne; quality of life; CADI; QUALITY-OF-LIFE; VULGARIS; QUESTIONNAIRE; VALIDATION; VERSION